2013
DOI: 10.1037/a0033247
|View full text |Cite
|
Sign up to set email alerts
|

Combining imagination and reason in the treatment of depression: A randomized controlled trial of internet-based cognitive-bias modification and internet-CBT for depression.

Abstract: Objective: Computerized cognitive-bias modification (CBM) protocols are rapidly evolving in experimental medicine yet might best be combined with Internet-based cognitive behavioral therapy (iCBT). No research to date has evaluated the combined approach in depression. The current randomized controlled trial aimed to evaluate both the independent effects of a CBM protocol targeting imagery and interpretation bias (CBM-I) and the combined effects of CBM-I followed by iCBT. Method: Patients diagnosed with a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 34 publications
5
109
1
3
Order By: Relevance
“…In addition, CBM procedures have been extended by training procedures targeting the induction and modification of functional and dysfunctional approach avoidance tendencies (e.g., Becker et al 2014;Rinck et al 2013;Wiers et al 2011), and standard experimental designs have been supplemented by single-case (e.g., Blackwell and Holmes 2010;Kruijt et al 2013) and qualitative (e.g., Beard et al 2012) methodologies. Finally, researchers have started to examine the effects of CBM procedures in conjunction with, or in comparison to, other psychological interventions such as internet-delivered cognitive behavioural therapy (e.g., Boettcher et al 2014;Bowler et al 2012;Månsson et al 2013;Williams et al 2013).…”
mentioning
confidence: 99%
“…In addition, CBM procedures have been extended by training procedures targeting the induction and modification of functional and dysfunctional approach avoidance tendencies (e.g., Becker et al 2014;Rinck et al 2013;Wiers et al 2011), and standard experimental designs have been supplemented by single-case (e.g., Blackwell and Holmes 2010;Kruijt et al 2013) and qualitative (e.g., Beard et al 2012) methodologies. Finally, researchers have started to examine the effects of CBM procedures in conjunction with, or in comparison to, other psychological interventions such as internet-delivered cognitive behavioural therapy (e.g., Boettcher et al 2014;Bowler et al 2012;Månsson et al 2013;Williams et al 2013).…”
mentioning
confidence: 99%
“…En otro caso, la combinación de TCC y MSC-A frente a la TCC combinada con relajación no arrojó resultados superiores en una muestra con fobia social (Shechner et al, 2014). Sin embargo, como se ha indicado previamente, la combinación de MSC-I con TCC sí ha mostrado ser superior al entrenamiento MSC-I aislado y a la no intervención en población con depresión (Williams et al, 2013). Además, un entrenamiento atencional hacia caras felices vs. de enfado (usando un procedimiento de dot probe), previo a una terapia para fobias infantiles, parece aumentar el efecto de dicha terapia (Waters et al, 2014).…”
Section: Discussionunclassified
“…Una variante utilizada del MSC-I basado en imaginación ha resultado de su combinación con la terapia cognitivo-conductual (TCC) por internet. Un ensayo clínico aleatorizado ha arrojado resultados superiores del grupo de intervención combinada, frente al grupo control y al de entrenamiento MSC-I aislado, tanto en síntomas depresivos como en el cambio clínicamente significativo (Williams, Blackwell, Mackenzie, Holmes y Andrews, 2013). Aunque se trata del primer estudio en este sentido, abre las puertas al enriquecimiento de los tratamientos eficaces disponibles al combinarlos con procedimientos de MSC.…”
Section: Almudena Duque Irene López-gómez Iván Blanco Y Carmelo Vázunclassified
“…Three studies (18,19,20) evaluated bias modification for depressive disorders but one study (Williams D et al, 2013) (18) (19) found a significant reduction in the overall anhedonia scores.…”
Section: Depressive Disorders (3 Studies)mentioning
confidence: 99%